Some results on fuzzy subsets in gamma-nearrings - Williams, D.R.Pr.; Dheena, P.; Latha, K.B.; Chandrasekeran, E. (Український математичний вісник, 2009)
In this paper, we introduce the notions of bi-ideal, quasi-ideal and residual quotient sets in terms of fuzzy subsets and have studied their related properties. Also, we have characterized residual quotient fuzzy subsets in gamma-nearrings.